You are where you live: parasitic nematode mitochondrial genome size is associated with the thermal environment generated by hosts. (3rd January 2013) - Lagisz, M.; Poulin, R.; Nakagawa, S.
Abstract There exists remarkable interspecific variation in mitochondrial sequence evolution rates and in mitochondrial genome sizes. A number of hypotheses based on the forces of mutation and selection have been proposed to explain this variation. Among such hypotheses, we test three: 1) the 'longevity‐dependent selection', 2) the 'functional constraints' and 3) the 'race for replication' hypotheses, using published mtDNA genomic sequences of 47 Nematoda species. We did not find any relationship between body size (used as a proxy for longevity) and genome size or the substitution rate of protein sequences, providing little evidence for the first hypothesis. Parasitic species from different thermal habitats, as determined by their definitive host type (ectothermal vs. endothermal), did not differ in their rates of protein evolution. Therefore, little support was obtained for the second hypothesis. However, we revealed that mitogenomes of parasites of endotherms were significantly smaller than those of parasites of ectotherms, supporting the race for replication hypothesis. As mitochondrial genomes of endothermal animals are usually more compact than those of ectothermal animals, intriguingly, nematode parasites of endotherms and ectotherms exhibit similar patterns of mtDNA length variation to their hosts.